The Community Service of Coconut Fish Floss Business Group in Tamedan Village, Tual City: Pengabdian Masyarakat kelompok usaha Abon Ikan Kelapa di Desa Tamedan Kota Tual - Hasyim, Cawalinya Livsanthi; Ngangun, Tati Atia; Rahael, Kristina Priskila; Rahantoknam, Meyske Angel; Madubun, Usman; Matdoan, Firmansyah; Taweatubun, Madina; Rettob, Wa Asri (Universitas Lancang Kuning, 2024)
Tamedan Village is one of the fish producing villages so obtaining raw materials for making fish floss is very easy to obtain. The partner for this activity is the coconut fish floss business group, which is still making shredded meat in a simple way due to a lack of knowledge about the shredded mixer tool which can speed up the processing process, the product packaging is also still very simple and has not been able to market its products widely due to limited knowledge about marketing activities and the lack of it. partner's understanding of business management and there is no bookkeeping yet. The aim of this service activity is Technology Transfer for using tools to make coconut fish floss to make it more practical. Carrying out counseling, training and demonstrations as well as assistance regarding the shredded production process using a shredded mixer, using labeled packaging and simple bookkeeping training. The results of this service activity can provide an understanding of shredded mixer tools, provide skills in processing fish floss and packaging with labels so that the product loks attractive and can increase sales and partner understanding in terms of financial recording.